Development and Validation of an Online Program for Promoting Self-Management among Korean Patients with Chronic Hepatitis B - Jinhyang Yang (Nursing Research and Practice)
The hepatitis B virus is second only to tobacco as a known human carcinogen. However, chronic hepatitis B usually does not produce symptoms and people feel healthy even in the early stages of live cancer. Therefore, chronically infected people should perceive it as a serious health problem and move on to appropriate health behaviour. The purpose of this paper is to develop and validate an online program for promoting self-management among Korean patients with chronic hepatitis B. The online program was developed using a prototyping approach and system developing life cycle method, evaluated by users for their satisfaction with the website and experts for the quality of the site. To evaluate the application of the online program, knowledge and self-management compliance of the subjects were measured and compared before and after the application of the online program. There were statistically significant increases in knowledge and self-management compliance in the user group. An online program with high accessibility and applicability including information, motivation, and behavior skill factors can promote self-management of the patient with chronic hepatitis B. Findings from this study allow Korean patients with chronic hepatitis B to engage in proactive and effective health management in the community or clinical practice.